Esterase‐Sensitive Prodrugs with Tunable Release Rates and Direct Generation of Hydrogen Sulfide1. Issue 14 (28th January 2016) - Zheng, Yueqin; Yu, Bingchen; Ji, Kaili; Pan, Zhixiang; Chittavong, Vayou; Wang, Binghe
Abstract: Prodrugs that release hydrogen sulfide upon esterase‐mediated cleavage of an ester group followed by lactonization are described herein. By modifying the ester group and thus its susceptibility to esterase, and structural features critical to the lactonization rate, H2 S release rates can be tuned. Such prodrugs directly release hydrogen sulfide without the involvement of perthiol species, which are commonly encountered with existing H2 S donors. Additionally, such prodrugs can easily be conjugated to another non‐steroidal anti‐inflammatory agent, leading to easy synthesis of hybrid prodrugs. As a biological validation of the H2 S prodrugs, the anti‐inflammatory effects of one such prodrug were examined by studying its ability to inhibit LPS‐induced TNF‐α production in RAW 264.7 cells. This type of H2 S prodrugs shows great potential as both research tools and therapeutic agents. Abstract : Tunable H2 S supply : Prodrugs that release hydrogen sulfide upon esterase‐mediated cleavage of an ester group followed by lactonization are described (see example). By modifying the ester group and thus its susceptibility to esterase H2 S release rates can be tuned. The anti‐inflammatory effects of one candidate were examined by studying its ability to inhibit TNF‐α production in RAW 264.7 cells.